EFEKTIVITAS SISTEM DISTRIBUSI PUPUK DI KABUPATEN MALANG - Susilowati, Dwi (Faculty of Economics and Business, University of Muhammadiyah Malang, 2011)
The research purpose is to understand level and factor in the failure of fertilizer distribution systembased on minister of industry and commerce instrution No. 70/MPP/Kep/2/2003. To determine the effectiveness of fertilizer distribution system , the author the ratio between the average expected targets and the reality. The results of this research is c2 about 0.500 with the values of c 2 tables around 11.34, significant at the 0.001 level in the region of Ho is received. The conclution is effective distribution of fertilizers rely on the right circumstances, that consist of time, quantity, price, quality, location and type.